2002
DOI: 10.1046/j.1365-2362.2002.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between Helicobacter pylori and atherosclerosis cannot be explained by a high homocysteine concentration

Abstract: This study shows a relationship between a positive immunoglobulin G antibody titre against H. pylori and PAD in young women. Moreover, this study does not support the hypothesis that H. pylori infection is related to atherosclerosis via an increase in plasma homocysteine concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…Some studies demonstrated an association between H. pylori infection and hyperhomocysteinemia 1-4, while the other studies did not. 15, 16, 21-23.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies demonstrated an association between H. pylori infection and hyperhomocysteinemia 1-4, while the other studies did not. 15, 16, 21-23.…”
Section: Discussionmentioning
confidence: 98%
“…The levels of Hcy in circulation are inversely related to renal function [8]. The association between Hcy and cardiovascular diseases [9, 10] and dementia [11, 12] has been shown in several studies, but is controversial [13, 14]. The cut-off value for the Hcy concentration used to define hyperhomocysteinemia is poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Even higher cobalamin levels were reported by Bloemenkamp et al [24] in H. pylori-positive subjects in a study including women with peripheral artery disease and controls. Since the latter two studies also investigated homocysteine, they are described in detail below.…”
Section: Helicobacter and Subclinical Cobalamin Deficiencymentioning
confidence: 56%
“…No difference in homocysteine according to H. pylori status was found in 150 women with peripheral artery disease and 412 control women [24]. H. pylori was diagnosed by positive IgG antibody test.…”
Section: Is Helicobacter Infection Related To Hyperhomocysteinaemia?mentioning
confidence: 92%
See 1 more Smart Citation